2018
DOI: 10.1136/jmedgenet-2017-105120
|View full text |Cite
|
Sign up to set email alerts
|

New insights into SERCA2a gene therapy in heart failure: pay attention to the negative effects of B-type natriuretic peptides

Abstract: Sarcoplasmic/endoplasmic reticulum calcium ATPase 2a (SERCA2a) is a target of interest in gene therapy for heart failure with reduced ejection fraction (HFrEF). However, the results of an important clinical study, the Calcium Upregulation by Percutaneous Administration of Gene Therapy in Cardiac Disease (CUPID) trial, were controversial. Promising results were observed in the CUPID 1 trial, but the results of the CUPID 2 trial were negative. The factors that caused the controversial results remain unclear. Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…In fact, SERCA2a gene therapy was shown in vitro to improve the contractile function of human cardiomyocytes isolated from patients afflicted with heart failure and is being tested as a new therapy for heart failure patients. (11)(12)(13) Thus, an in vitro model of human ischemic heart failure should present with reduced contraction, reduced calcium flux amplitudes, reduced SERCA2a protein expression, prolonged calcium transient duration, prolonged action potential duration and reduced PLN phosphorylation. Additionally, the functional phenotype should be rescued using established SERCA2a gene therapy approaches known to improve cardiomyocyte contractile function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, SERCA2a gene therapy was shown in vitro to improve the contractile function of human cardiomyocytes isolated from patients afflicted with heart failure and is being tested as a new therapy for heart failure patients. (11)(12)(13) Thus, an in vitro model of human ischemic heart failure should present with reduced contraction, reduced calcium flux amplitudes, reduced SERCA2a protein expression, prolonged calcium transient duration, prolonged action potential duration and reduced PLN phosphorylation. Additionally, the functional phenotype should be rescued using established SERCA2a gene therapy approaches known to improve cardiomyocyte contractile function.…”
Section: Introductionmentioning
confidence: 99%
“…SERCA2a gene overexpression in the heart rapidly hastens the removal of cytosolic calcium during diastole, thus alleviating diastolic dysfunction. In fact, SERCA2a gene therapy was shown in vitro to improve the contractile function of human CMs isolated from patients afflicted with heart failure and is being tested as a new therapy for patients with heart failure ( 11 13 ). Thus, an in vitro model of human ischemic heart failure should present with reduced contraction, reduced calcium flux amplitudes, reduced SERCA2a protein expression, prolonged calcium transient duration (CaTD), prolonged action potential duration (APD), and reduced PLN phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the RAS-MAPK pathway regulates SERCA2A, PLN, and LTCC expression that is downregulated during hypertrophy and heart failure [6,27,28]. Consistently, an increase in BNP, which is known as a HCM biomarker, leads to a decrease in SERCA2A expression [70].…”
Section: Altered Cardiac Calcium Handling In Raf1 S257l Cardiomyocytesmentioning
confidence: 68%
“…Its fundamental role in excitation–contraction coupling makes calcium handling central to pathophysiological and adaptive mechanisms of defective contractile function and impaired relaxation in cardiomyopathy. Several studies have demonstrated reduced sarcoendoplasmic reticulum calcium storage and release, with decreased SERCA2a and upregulated sodium–calcium exchanger activity 15. Altered expression and activity of voltage-gated L-type calcium channels in heart failure and hypertrophy observed in several studies are incompletely understood,16 although highlight the centrality of calcium handling to cardiomyocyte dysfunction.…”
Section: Calcium-dependent Myocardial Contrast Imagingmentioning
confidence: 99%